A reliable and flexible data gathering protocol for battery limited wireless sensor networks. (1st January 2013) - Wu, Celimuge; Ohzahata, Satoshi; Kato, Toshihiko
In this paper, we consider a wireless sensor network (WSN) for a clinical purpose. However, due to the fading in wireless communications and limited battery power of electronic devices, providing an efficient and reliable communication is extremely challenging. As a solution, we propose fuzzy one-phase pull (FOPP), a fuzzy logic-based one-phase pull protocol. The protocol considers signal strength, route length and residual energy in the route selection. The protocol employs a fuzzy logic to consider these metrics jointly. Since the parameters and the rules used in the fuzzy logic are reconfigurable, the proposed protocol can be used in any scenarios by simple parameter tuning. We also propose two mechanisms (timeout retransmission mechanism and double-path mechanism) to further improve the reliability of the protocol. We use computer simulations to evaluate the performance of the proposed protocol.